Characteristics of Flow Hydrophysics Variables and Flood Potential Around Kuala Jengki Estuary, Manado City - Maxi Tendean,; Grace F. E. Suoth,; Yolanda Mona Salainti,; Arie Supriati,; Hetreda Terry, (Technium Social Sciences Journal, 2024)
Flood disasters along the river resulted from damage to flood barrier construction along the river bank.The damage to the flood retaining wall is technically caused by the very large hydrophysical parameters of the river flow.In theory, the flow mass density parameter shows the concentration of sediment transported through one cross-section.As a result of changes in the volume of sediment transport, there will be an increase in flow energy, followed by changes in large water masses, and this is seen as a destructive force component in some equivalent places or riverbanks, which can physically be formulated in the form of a model function.It is important to do a map of the hydrophysical character variable flowand flood potential along KualaJengki estuary Manado City, it is important to do because the estuary is often flooded. Measurement of the hydrophysical variable mass flow density was carried out at a depth of 0.6 rivers at high and low tides.The mass density of the flow is the mass of water containing transport sediment divided by its volume.The mass of water (sample) is measured using a scale, while the volume is measured using a measuring cup or another container that has a volume measurement.For the presentation of density data profiles and other analytical purposes, the measured data were reproduced using linear interpolation techniques.The mass density data modeling was carried out using an experimental function iteration technique containing constants. The results of the research at high tide, the position which is approximately 275 meters at measurement points 10 to 13 at a distance of 675 meters to 950 meters becomes a location that is very prone to river lip damage if there is a rise in water level due to high rainfall, or a position where it becomes flood-prone when the flow density increases, along with an increase in the volume of river water, which is followed by changes in river flow velocity carrying various types of sediment.At a distance of 165 meters at low tide, the measurement position is between 10 and 13, there is an increase in large flow discharge accompanied by an increase in flow velocity that carries flow mass (mass density) with various types of sediment transport.In this condition, the location which is 165 meters away according to the model map becomes prone to river lip damage, which means that it is a location that has the potential for flooding.In contrast to measurement positions 5 and 6 at high tide, there is a significant increase in the low mass density, while at low tide this condition does not occur, this is because the flow velocity at low tide does not change significantly, causing the mass flow density to be relatively the same.